Coming to America : the story of immigration - Maestro, Betsy; Ryan, Susannah (New York, New York : Scholastic, 1996)
Explores the evolving history of immigration to the United States, a long saga about people coming first in search of food and then, later in a quest for religious and political freedom, safety, and prosperity
Elementary Grade
890
Accelerated Reader
Reading Counts!
Keywords: Ellis Island Immigration Station (N.Y. and N.J.) -- History -- Juvenile literature; Ellis Island Immigration Station (New York, N.Y.) -- History; Immigrants -- United States -- History -- Juvenile literature; Immigrants; United States -- Emigration and immigration -- History -- Juvenile literature; United States -- Emmigration and immigration -- History; Nonfiction; Literature